1996
DOI: 10.1002/art.1780390719
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte infiltration in synovial tissue from the shoulder of patients with polymyalgia rheumatica. Quantitative analysis and influence of corticosteroid treatment

Abstract: Objective: To investigate the immunologic features of synovitis in patients with polymyalgia rheumatica (PMR) and to assess the modifications induced by corticosteroids.Methods. Arthroscopic biopsies of shoulder synovium were obtained from 12 patients with untreated PMR and from 7 patients with PMR that had been treated. Immunohistochemistry was performed on frozen sections utilizing a panel of monoclonal antibodies and computerized image analysis.Results. Synovitis was present in 10 of 12 (83%) untreated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 24 publications
4
65
1
6
Order By: Relevance
“…With regard to the pathophysiology of PMR, the prevailing view today is that the symptoms of PMR are caused by inflammatory processes occurring in synovial structures (10,(12)(13)(14)(15)(16). However, imaging evidence of synovial inflammation does not entirely correlate with the clinical findings (2,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the pathophysiology of PMR, the prevailing view today is that the symptoms of PMR are caused by inflammatory processes occurring in synovial structures (10,(12)(13)(14)(15)(16). However, imaging evidence of synovial inflammation does not entirely correlate with the clinical findings (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the paucity of laboratory evidence of muscle and vascular abnormalities, as well as on the histologic, MRI, computed tomography, ultrasound, and FDG-PET evidence from the shoulder and hip joints (3,10,(12)(13)(14) and the spinal column (2,12), the predominant view has, in recent years, been that the symptoms in patients with PMR reflect bursitis and synovitis (12,15,16). However, PMR symptoms may be seen in the absence of imaging evidence of inflammation, and conversely, such evidence may be present in the absence of symptoms of PMR or may remain after such symptoms have disappeared (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, arthroscopic studies have confirmed the presence of synovitis in the proximal joints of PMR patients (8). Moreover, magnetic resonance imaging and ultrasonography have disclosed inflammation of subacromial and subdeltoid bursae in association with synovitis of the glenohumeral joints and tenosynovitis of the biceps, as well as the presence of trochanteric, iliopsoas, ischiogluteal, and low cervical interspace bursitis in patients with PMR (9 -12).…”
Section: Epidemiology Of Gca and Pmrmentioning
confidence: 99%
“…Although corticosteroids rapidly control PMR clinical manifestations, patients often require corticosteroid therapy for at least 2 years, with potential multiple side effects [1]. Synovitis is a major cause of musculoskeletal symptoms in PMR [2], but the pathomechanisms leading to synovial lesion are not well known.…”
Section: Introductionmentioning
confidence: 99%